(untitled) (IMC Journal of Medical Science, 2018)
A case of concurrent chikungunya virus and dengue virus infection is reported here. The patient presented with fever and generalized body ache. Diagnostic work-up revealed chikungunya-dengue co-infection. Dengue is endemic in Bangladesh while chikungunya is a recently emerging infection. As both the viruses are transmitted by a common vector, Aedes spp., such co-infections are likely to increase in coming years. IMC J Med Sci 2018; 12(1): 42-43